Alat Uji Karbon Dioksida Pada Kopi Sebagai Indikator Kelayakan Untuk Dikonsumsi - Habbi Yazid (Ikatan Ahli Informatika Indonesia, 2021)
Carbon dioxide Test Equipment on Brewed Coffee Powder as an Indicator of Feasibility for Consumption Free Microcontroller is a tool used to measure carbon dioxide levels of roasted coffee and which will be consumed. This tool uses the MG-811 as a sensor to determine the carbon dioxide level in the brewed coffee, and is also equipped with a buzzer that will turn on when the carbon dioxide level in the coffee is high or unfit for consumption. Then there is an LCD that will display the level of carbon dioxide in the coffee and there is also an LED consisting of 3 colors, if it is red then the carbon dioxide level is too high and not suitable for consumption, if it is yellow then the carbon dioxide level is not too high but not feasible for consumption and the green color indicates low carbon dioxide levels and coffee is suitable for use. For the controller of this tool using Arduino UNO.